CUX2, BRAP and ALDH2 are associated with metabolic traits in people with excessive alcohol consumption - Chen, I-Chun; Kuo, Po-Hsiu; Yang, Albert C.; Tsai, Shih-Jen; Liu, Tung-Hsia; Liu, Hung-Jen; Lan, Tsuo-Hung; Chen, Hong-Ming; Huang, Huang-Nan; Chung, Ren-Hua; Liu, Yu-Li (Scientific reports, 2020)
Molecular mechanisms that prompt or mitigate excessive alcohol consumption could be partly explained by metabolic shifts. This genome-wide association study aims to identify the susceptibility gene loci for excessive alcohol consumption by jointly measuring weekly alcohol consumption and γ-GT levels. We analysed the Taiwan Biobank data of 18,363 Taiwanese people, including 1945 with excessive alcohol use. We found that one or two copies of the G allele in rs671 ( ALDH2 ) increased the risk of excessive alcohol consumption, while one or two copies of the C allele in rs3782886 ( BRAP ) reduced the risk of excessive alcohol consumption. To minimize the influence of extensive regional linkage disequilibrium, we used the ridge regression. The ridge coefficients of rs7398833, rs671 and rs3782886 were unchanged across different values of the shrinkage parameter. The three variants corresponded to posttranscriptional activity, including cut-like homeobox 2 (a protein coded by CUX2 ), Glu504Lys of acetaldehyde dehydrogenase 2 (a protein encoded by ALDH2 ) and Glu4Gly of BRCA1-associated protein (a protein encoded by BRAP ). We found that Glu504Lys of ALDH2 and Glu4Gly of BRAP are involved in the negative regulation of excessive alcohol consumption. The mechanism underlying the γ-GT-catalytic metabolic reaction in excessive alcohol consumption is associated with ALDH2 , BRAP and CUX2 . Further study is needed to clarify the roles of ALDH2 , BRAP and CUX2 in the liver–brain endocrine axis connecting metabolic shifts with excessive alcohol consumption .